Stem Cell Mesenchymal Injection Increases Platelet-Derived Growth Factors Level and Percentage of Collagen in Third-Degree Burn injured Mice - Ridawati, Erna; Nasihun, Taufiqurrachman; Wiratno, Wiratno (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2016)
Introduction: Mesenchymal stem cell (MSC) has been demonstrated to accelerate wound healing. Platelet-derived growth factor (PDGF) and collagen have an important role in wound healing. However, the effect of MSC on levels of PDGF and number of collagen has not been established. Objectives: To determine the effect of MSC on the levels of PDGF and the percentage of collagen in the burns healing. Methods: in this experimental study, 20 BALB /c mice were divided into 4 groups: a control group (G-0) injected with 2 ml of distilled water and group 1 (G-1), Group 2 (G-2), and group 3 (G- 3) injected with MSC at the dose of 1 x 104, 2 x 104, and 4 x 104 respectively. The burn wound was made by attaching a metal nail that had been heated for 20 seconds at the feet of mice. Levels of PDGF on day 2 (PDGF-2) and 7 (PDGF-7) was assessed by ELISA, while on day 10 excision of skin was done to calculate the percentage of collagen. Results: There was a significant difference in the levels of PDGF-2, PDGF-7, and the percentage of collagen ( P <0.05). Posthoc analysis showed that the levels of PDGF-2, PDGF-7, and percentage of collagen in the G-2 and G-3 was significantly higher than that of G-0, p <0.05. While the levels of PDGF-2, PDGF-7, and the percentage of collagen in the G-3 was significantly higher than that of G-2 and G-1 (p <0.05). Conclusion: Injection of MSC at a dose of 2 x 1044 and 4 x 1044 increases the levels of PDGF and the percentage of collagen.